Nanostructures on Fluoropolymer Nanotextile Prepared Using a High-Energy Excimer Laser - Slepička, Petr; Slepičková Kasálková, Nikola; Fajstavr, Dominik; Frýdlová, Bára; Sajdl, Petr; Kolská, Zdeňka; Švorčík, Václav (Materials (Basel, Switzerland), 2023)
This study is focused on polytetrafluoroethylene (PTFE) porous nanotextile and its modification with thin, silver sputtered nanolayers, combined with a subsequent modification with an excimer laser. The KrF excimer laser was set to single-shot pulse mode. Subsequently, the physico chemical properties, morphology, surface chemistry, and wettability were determined. Minor effects of the excimer laser on the pristine PTFE substrate were described, but significant changes were observed after the application of the excimer laser to the polytetrafluoroethylene with sputtered silver, where the formation of a silver nanoparticles/PTFE/Ag composite was described, with a wettability similar to that of a superhydrophobic surface. Both scanning electron microscopy and atomic force microscopy revealed the formation of superposed globular structures on the polytetrafluoroethylene lamellar primary structure, which was also confirmed using energy dispersive spectroscopy. The combined changes in the surface morphology, chemistry, and thus wettability induced a significant change in the PTFE's antibacterial properties. Samples coated with silver and further treated with the excimer laser 150 mJ/cm2 inhibited 100% of the bacterial strain E. coli. The motivation of this study was to find a material with flexible and elastic properties and a hydrophobic character, with antibacterial properties that could be enhanced with silver nanoparticles, but hydrophobic properties that would be maintained. These properties can be used in different types of applications, mainly in tissue engineering and the medicinal industry, where water-repellent materials may play important roles. This synergy was achieved via the technique we proposed, and even when the Ag nanostructures were prepared, the high hydrophobicity of the system Ag-polytetrafluorethylene was maintained.
Keywords: antibacterial properties; laser exposure; morphology; wettability; silver nanolayer; nanostructure; PTFE; polymer